Incertidumbre de la medición de masa en la determinación de los parámetros de consumo de electrodos de recargue - Valdés Arencibia, Rosenda (2013)
This work presents the evaluation of the uncertainty of the measurements to determine the consumption parameters of hardfacing electrode, emphasizing the mass measurement. The experimentation was carried out obtaining deposits at three levels of current (120 A, 145 A y 160 A) and measuring the time spent in welding, the length of the welds the test plate and electrode mass (initial and final). Based on these results, the consumption parameters were also determined. The uncertainty related to the measurements the mass of the samples, the mass consumption of the electrode, the deposited mass and consumption parameters was determined. The results showed that the deposition efficiency increase as a function of the current, turning the best result (74.12 %) at 120 A. The expanded measurement uncertainty associated to consumption parameters changed between 1.47% and 2.41% for the deposition efficiency, 0.4 g/min and 0.6 g/min for the consumption rate vary of 0.6 g/min to 0.7 g/min for the deposition rate.